Mouth dissolving tablets II: An overview of evaluation techniques - Shukla D.; Chakraborty S.; Singh S.; Mishra B. (My University, 2025)
Mouth dissolving tablets are well established dosage forms available in the market. The numerous advantages that they offer to the patients in terms of compliance as well as to the manufacturers in terms of huge revenues by line extension of products are well known. In spite of such popularity, there seems to be lack of a standardized system to characterize these dosage forms. Enormous work has been done in this field, wherein some of the researchers have developed their own methods of evaluation. This article attempts to present a detailed review regarding technological advances made so far in the area of evaluation of mouth dissolving tablets with respect to special characteristics of these unique dosage forms. In the absence of any available standardized method, the author's recommendation on critical issues in the field may be considered. © Shukla et al.; licensee Österreichische Apotheker-Verlagsgesellschaft m. b. H.